SARS-CoV-2 and other viruses in soil: An environmental outlook - Anand, Uttpal (Environ Res, 2021)
In the present review, the authors shed light on the SARS-CoV-2 impact, persistence, and monitoring in the soil environment. With this purpose, several aspects have been deepened: i) viruses in soil ecosystems; ii) direct and indirect impact on the soil before and after the pandemic, and iii) methods for quantification of viruses and SARS-CoV-2 monitoring in soil. Viruses are present in soil (i.e. up to 417 × 10(7) viruses per g TS(−1) in wetlands) and can affect the behavior and ecology of other life forms (e.g. bacteria), which are remarkably important for maintaining environmental equilibrium. Also, SARS-CoV-2 can be found in soil (i.e. up to 550 copies·g(−1)). Considering that the SARS-CoV-2 is very recent, poor knowledge is available in the literature on persistence in the soil and reference has been made to coronaviruses and other families of viruses. For instance, the survival of enveloped viruses (e.g. SARS-CoV) can reach 90 days in soils with 10% of moisture content at ambient. In such a context, the possible spread of the SARS-CoV-2 in the soil was evaluated by analyzing the possible contamination routes.